The impact of Corporate Social Responsibility on the performance of European firms - Fernandes, Patrícia Joana Gonçalves Queiroga (2019)
This thesis investigates the relationship between a firm’s corporate social responsibility performance (CSR) and its financial performance in a European context. In order to evaluate this relationship, CSR performance is estimated through companies’ ESG scores, while financial performance is represented by the Return on Assets and Return on Equity Ratios, and Tobin’s Q is used as a proxy for firm value. Evidence is found that CSR performance and firm financial performance/value are positively correlated. However, the direction of causality is left to be determined. The findings suggest as well that top performers in CSR have higher returns than their peers with a lower CSR performance. Notwithstanding, no evidence is found that firms with the worst CSR performance are linked with worse financial results. Finally, the results indicate that the three pillars of ESG (Environmental, Social and Corporate Governance) have different significant relationships with firm value and financial performance. Environmental performance depicts a negative correlation with firm value and financial results, while Social and Corporate Governance performance are positively linked with the corporate financial performance indicators and with firm value.